2020
DOI: 10.3390/ijms21197043
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of CsATGs in Tea Plant and the Involvement of CsATG8e in Nitrogen Utilization

Abstract: Nitrogen (N) is a macroelement with an indispensable role in the growth and development of plants, and tea plant (Camellia sinensis) is an evergreen perennial woody species with young shoots for harvest. During senescence or upon N stress, autophagy has been shown to be induced in leaves, involving a variety of autophagy-related genes (ATGs), which have not been characterized in tea plant yet. In this study, a genome-wide survey in tea plant genome identified a total of 80 Camellia Sinensis autophagy-related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The in-depth study of autophagy in TB contributes to understanding the molecular mechanism of plant response to abiotic stress and promotes the breeding of excellent stress-resistant varieties. Besides Arabidopsis , autophagy genes are also found in higher plants, such as 32 OsATGs in rice [ 19 ], 26 CsATGs in Sweet Orange [ 20 ], 80 CsATGs in tea [ 21 ], etc. We screen 49 FtATGs genes in the TB genome.…”
Section: Discussionmentioning
confidence: 99%
“…The in-depth study of autophagy in TB contributes to understanding the molecular mechanism of plant response to abiotic stress and promotes the breeding of excellent stress-resistant varieties. Besides Arabidopsis , autophagy genes are also found in higher plants, such as 32 OsATGs in rice [ 19 ], 26 CsATGs in Sweet Orange [ 20 ], 80 CsATGs in tea [ 21 ], etc. We screen 49 FtATGs genes in the TB genome.…”
Section: Discussionmentioning
confidence: 99%
“…The harvest of T3 seeds and the method for hydroponic culture were conducted as described previously ( Huang et al, 2020 ). Three weeks after transferring from the petri dish, plants were divided into two groups and treated with LN (Low N, 0.125 mM NH 4 NO 3 ) and NN (normal N, 2.5 mM NH 4 NO 3 ), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In tea plants, CsATG101 is a single copy ( Huang et al, 2020 ). It was reported that the expression level of CsATG101 changed with abiotic stress, such as drought and cold ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Still, it was possible to detect that CsNRT2 participated in NO 3 − transport under low N conditions ( Hu et al., 2023 ; Lin et al., 2023b ). The AuTophaGy-related genes CsATG8e and CsATG3a were linked to an improved plant ability for N recycling and tolerance to low N levels ( Huang et al., 2020 ; Huang et al., 2023a ). These genes emerge as promising indicators and may contribute to identifying higher NUE among various germplasm resources.…”
Section: An Overview Of Nitrogen Use Efficiency Assessment By Tea Plantsmentioning
confidence: 99%